Central Diabetes Insipidus as a Complication of Meningitis in the Intensive Care Unit: A Case Report - Liliriawati Ananta Kahar (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: Central diabetes insipidus (CDI) is a rare neuroendocrine complication of meningitis caused by hypothalamic–pituitary dysfunction, leading to severe fluid and electrolyte imbalances in critically ill patients. Objective: This study aims to describe the clinical presentation, diagnostic approach, and management of CDI as a complication of meningitis in a critically ill ICU patient and to raise awareness of neuroendocrine sequelae in neurocritical care. Methods: This study is a case report describing the clinical course of a single patient. Data were obtained from medical records, including symptoms, physical examination findings, laboratory results, and treatment interventions, and were analyzed descriptively in accordance with CARE guidelines, with patient anonymization maintained. Results: A 34-year-old woman was admitted to the ICU with progressive decreased consciousness and was diagnosed with subacute tuberculous meningitis based on clinical and cerebrospinal fluid findings. She initially presented with hyponatremia (serum sodium, 124 mEq/L), followed by persistent polyuria (>3 mL/kg/hour) with rising serum sodium levels (136 mEq/L) on day 3, reflecting a biphasic AVP disturbance pattern. CDI was confirmed based on clinical criteria and a positive response to desmopressin. Management included fluid resuscitation, electrolyte correction, desmopressin administration, antituberculosis therapy, and broad-spectrum antibiotics, resulting in gradual clinical stabilization. Conclusion: CDI should be recognized as a potential complication of severe meningitis. Early identification through serial monitoring of urine output, serum sodium, and osmolality—combined with prompt differentiation from syndrome of inappropriate antidiuretic hormone secretion (SIADH) and cerebral salt wasting—is essential to prevent hemodynamic instability and secondary brain injury. A multidisciplinary approach is critical for optimal neurocritical care management.